Motivational salience and genetic variability of dopamine D2 receptor expression interact in the modulation of interference processing - Richter, Anni; Richter, Sylvia; Barman, Adriana; Soch, Joram; Klein, Marieke; Assmann, Anne; Libeau, Catherine; Behnisch, Gusalija; Wüstenberg, Torsten; Seidenbecher, Constanze I.; Schott, Björn H. (Frontiers in Human Neuroscience, 2013)
Dopamine has been implicated in the fine-tuning of complex cognitive and motor function and also in the anticipation of future rewards. This dual function of dopamine suggests that dopamine might be involved in the generation of active motivated behavior. The DRD2 TaqIA polymorphism of the dopamine D2 receptor gene (rs1800497) has previously been suggested to affect striatal function with carriers of the less common A1 allele exhibiting reduced striatal D2 receptor density and increased risk for addiction. Here we aimed to investigate the influences of DRD2 TaqIA genotype on the modulation of interference processing by reward and punishment. 46 young, healthy volunteers participated in a behavioral experiment, and 32 underwent functional magnetic resonance imaging (fMRI). Participants performed a flanker task with a motivation manipulation (monetary reward, monetary loss, neither, or both). Reaction times (RTs) were shorter in motivated flanker trials, irrespective of congruency. In the fMRI experiment motivation was associated with reduced prefrontal activation during incongruent versus congruent flanker trials, possibly reflecting increased processing efficiency. DRD2 TaqIA genotype did not affect overall RTs, but interacted with motivation on the congruency-related RT differences, with A1 carriers showing smaller interference effects to reward alone and A2 homozygotes exhibiting a specific interference reduction during combined reward and punishment trials. In fMRI, anterior cingulate activity showed a similar pattern of genotype-related modulation. Additionally, A1 carriers showed increased anterior insula activation relative to A2 homozygotes. Our results point to a role for genetic variations of the dopaminergic system in individual differences of cognition-motivation interaction.